(untitled) (Herald of the National Children’s Medical Center, 2024)
Abstract: This study investigates the morphological alterations in the gastric mucosa caused by chronic nicotine intoxication and evaluates the effectiveness of two detoxification agents, Super Omega and Mumie-LIK. The experiment was conducted on laboratory animals subjected to prolonged nicotine exposure, with subsequent analysis of histological and morphometric changes in the gastric mucosa. Findings revealed significant pathological alterations, including epithelial damage, inflammatory infiltration, and impaired regenerative capacity of the mucosa. Both detoxification agents demonstrated a positive therapeutic effect, with Mumie-LIK showing a superior ability to restore the structural integrity of the mucosa. These results highlight the potential clinical application of detoxification therapy for mitigating the harmful effects of nicotine. Materials and methods of research: The study involved 100 laboratory rats weighing 220–300 g, housed under standard vivarium conditions. The animals were divided into three groups: the control group (n = 20), which received physiological saline; the experimental group (n = 40), which received nicotine at doses of 0.5 mg/kg (n = 20) and 1.0 mg/kg (n = 20); and the treatment group (n = 40), where, after 8 weeks of intoxication, the animals received therapy with Mumie-LIK (n = 20) and Super Omega (n = 20). Results of the study: The study revealed that chronic administration of nicotine at doses of 0.5 mg/kg and 1.0 mg/kg induced significant toxic effects in laboratory rats, including marked weight loss, decreased motor activity, and alterations in behavior. Biochemical analyses showed increased levels of oxidative stress markers, including malondialdehyde (MDA), along with a reduction in antioxidant activity, such as glutathione levels and catalase activity. Therapeutic interventions with Mumie-LIK and Super Omega, administered after 8 weeks of nicotine exposure, demonstrated restorative effects. Both treatments improved weight gain, restored motor activity, and partially normalized oxidative stress biomarkers. Specifically, Mumie-LIK showed a notable reduction in MDA levels, while Super Omega was more effective in enhancing antioxidant activity and restoring biochemical homeostasis. Overall, Super Omega exhibited slightly higher therapeutic efficacy compared to Mumie-LIK in mitigating nicotine-induced damage, suggesting its potential as a complementary treatment in oxidative stress-related conditions.